2018
DOI: 10.1016/j.chembiol.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A Lysine Acetyltransferase Contributes to the Metabolic Adaptation to Hypoxia in Mycobacterium tuberculosis

Abstract: Summary Upon inhibition of respiration, which occurs in hypoxic or nitric oxide-containing host microenvironments, Mycobacterium tuberculosis (Mtb) adopts a non-replicating ‘quiescent’ state and becomes relatively unresponsive to antibiotic treatment. We used comprehensive mutant fitness analysis to identify regulatory and metabolic pathways that are essential for the survival of quiescent Mtb. This genetic study identified a protein acetyl-transferase (MtPat/Rv0998) that promoted survival and altered the flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…Many studies investigating antibiotic efficacy and new drug target discovery are performed in vitro . While it is possible to change discrete aspects of the culture conditions to mimic individual stresses ( 25 , 45 48 ), these models do not fully recapitulate the complex environment encountered by the bacterial population during infection. In this study, we identified genes important for bacterial survival under antibiotic pressure in the mouse model of TB, where the bacteria grow intracellularly ( 49 ) in the presence of a fully functional adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigating antibiotic efficacy and new drug target discovery are performed in vitro . While it is possible to change discrete aspects of the culture conditions to mimic individual stresses ( 25 , 45 48 ), these models do not fully recapitulate the complex environment encountered by the bacterial population during infection. In this study, we identified genes important for bacterial survival under antibiotic pressure in the mouse model of TB, where the bacteria grow intracellularly ( 49 ) in the presence of a fully functional adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed pellicle or pellicle-like biofilm formation in M. tuberculosis and M. smegmatis [59][60][61][62] . However, they identified groEL1, mutT3 (neighboring pknG), and malate dehydrogenase as genes that confer biofilm formation, which is contrary to our study results that identified them as non-essential with no significant fitness change under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…However, obligate aerobe bacteria stop growing without oxygen. Mycobacterium tuberculosis is a wellcharacterized example of an obligate aerobe bacterium and it enters a non-growing state when no oxygen is available (Rittershaus et al 2018). M. tuberculosis encounters hypoxic conditions upon infection of its host, since hypoxia is often a consequence of an immune response.…”
Section: Growth Arrest Due To Starvationmentioning
confidence: 99%